Receptive and Productive Collocational Knowledge, Vocabulary Size, Motivation, and Self-Efficacy in ESL Reading Comprehension - Husin, Nahazatul; Rawian, Rafizah (Masyarakat Linguistik Indonesia Universitas Andalas, 2025)
In reading research and pedagogy, it is important to understand the nuances of collocation competence in ESL learners’ reading comprehension of English-language learners, investigate the interrelationships, and evaluate the mutual effect. This study aimed to determine the relationship between receptive and productive collocational knowledge, vocabulary size, motivation, and reading comprehension performance of Royal Malaysian Air Force technicians, focusing on the setting of Institute Technology Aerospace (ITAS) in Kedah State in Malaysia. Using a quantitative design, three tests (receptive/productive collocations, vocabulary size) and two questionnaires (motivation, self-efficacy) were administered to 200 technicians studying English reading comprehension courses. These participants were selected through a random probability sampling technique to ensure an unbiased representation of the target population. Data were analysed descriptively and inferentially, conducting correlation and regression analyses. After determining the correlations, three regression models were conceived to evaluate the most contributing variable. The findings revealed that the receptive collocational knowledge of these ESL learners was the most predictive of their reading results, which briefly means that it enhances reading performance. Moreover, all variables had positive and significant correlations with reading performance. In contrast, receptive and productive collocational competence and vocabulary size had higher correlation values than motivation and self-efficacy. The study offers significant theoretical implications for the field of reading research, especially in the Southeast Asian region, and practical implications for teachers, learners, and assessors of ESL reading comprehension.